Abstracts Communications Orales – Cardiovasculaire_ JRANF 2025_JAIM 2025_17.3 - NTSIETANKAZI RENE MINION; S.B.M.G. ADJADOHOUN; Hamidou DEME; ZOUZOU ANGE ERIC; DIALLO Mamadou; Mbede Maggy; OMBOUMAHOU BAKALE FE, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
5- Abstracts Communications Orales – Cardiovasculaire_ JRANF 2025_JAIM 2025_17.3